1982
DOI: 10.2134/agronj1982.00021962007400030025x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of Daily Climatic Data for Agronomic Models1

Abstract: Many agronomic models require the input of daily climatic data. Simulated climatic data may be used when long series of historic data are not available or convenient, or when future data are needed. A stochastic weather simulation model was developed and validated for a wide range of climates. The model produces possible daily sequences of precipitation amount, maximum and minimum air temperature, and total solar radiation at the earth's surface for the entire year. A first‐order, two‐state Markov chain is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…Our results showed that this approach worked well for the climate conditions that were included in this study and were consistent with findings of others (Larsen & Pense 1982, Richardson & Wright 1984, Geng et al 1986, Wilks 1999, Sentelhas et al 2001, Hartkamp et al 2003. However, Schubert (1994), Wallis & Griffiths (1995), Semenov et al (1998), Hayhoe (2000, Puche & Silva (2001) Table 2.…”
Section: Precipitationsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that this approach worked well for the climate conditions that were included in this study and were consistent with findings of others (Larsen & Pense 1982, Richardson & Wright 1984, Geng et al 1986, Wilks 1999, Sentelhas et al 2001, Hartkamp et al 2003. However, Schubert (1994), Wallis & Griffiths (1995), Semenov et al (1998), Hayhoe (2000, Puche & Silva (2001) Table 2.…”
Section: Precipitationsupporting
confidence: 92%
“…Generated weather data can be used as input for hydrologic models for watershed planning, evaluation and design purposes (Richardson 1981) and for analysis of water resources (Hayhoe 2000). They can also be used in various types of agricultural man-agement models to assess the risks associated with different alternatives (Larsen & Pense 1982, Hayhoe 1998, O'Leary & Connor 1998. In a real-time mode, generated data can be used as future sequences in crop-simulation models for yield forecasting (Thornton et al 1997, Bannayan & Crout 1999, Georgiev & Hoogenboom 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the daily precipitation generator is a first-order two-state Markov chain (Larsen and Pense 1982, Roldom, J. and Woolhiser, DA 1982, Richardson 1985 and exponential and gamma distribution are used to generate the precipitation amount.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the number of parameters, Larsen and Pense (1981) fitted three parameter Sine curves to the mean daily maximum and minimum temperatures conditioned on the wet/dry state of the present day. The residuals of these two variables from their mean values for the two types of days were modelled by two bi-variate Normal distributions.…”
Section: Annual and Monthly Climate Datamentioning
confidence: 99%